2019
DOI: 10.3747/pdi.2018.00082
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Screening Peritoneal Dialysis Patients for Bacterial Colonization or Contamination

Abstract: Introduction The adoption of the International Society for Peritoneal Dialysis guideline of using mupirocin ointment has been limited by fear of developing mupirocin-resistant organisms. We performed a surveillance program of a large peritoneal dialysis (PD) unit. Methods We performed 1,175 surveillance swabs from anterior nares, PD catheter exit site, groin, and axilla, from 240 patients. The mean interval between swabs was 3.3 months. Results Colonization by Staphylococcus aureus ( S. aureus) or Pseudomonas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…3 Although it suggests "repeating wound swab for bacterial culture 1 to 2 weeks after discontinuation of antibiotic has been advocated", this is not part of ISPD guideline. We recently reported that colonization of exit site (ES) by Staphylococcus aureus or Pseudomonas (P) was associated with subsequent ESI 4 and introduced a policy to follow-up patients who developed ESI from these virulent pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…3 Although it suggests "repeating wound swab for bacterial culture 1 to 2 weeks after discontinuation of antibiotic has been advocated", this is not part of ISPD guideline. We recently reported that colonization of exit site (ES) by Staphylococcus aureus or Pseudomonas (P) was associated with subsequent ESI 4 and introduced a policy to follow-up patients who developed ESI from these virulent pathogens.…”
Section: Introductionmentioning
confidence: 99%